Пост-чернобыльский социум: риски и шансы выживания - Амджадин, Л.; Саенко, Ю.; Ходоровская, Н. (Социология: теория, методы, маркетинг, 2006)
The article analyzes social consequences of the Chornobyl catastrophe and ways of overcoming them from the viewpoint of more than twenty year experience. After reviewing the chronicle of events in brief, the authors dwell upon some crucial questions, such as radiological state of environment, structure of settlements, ecological, biological, medical, demographic, social and psychological consequences of the Chornobyl accident. Then attention is focused on social prospects for activity of victims’ communities. The Chornobyl mistakes and tasks for the future are also examined. It is emphasized that Ukraine has already turned down the “conception of risks” and started seeking and realizing the “scenarios of chances” for revival and development of suffered areas and communities. Implementation of these scenarios needs day- to -day efforts of international organizations, power structures, specialized institutions, local communities as well as private citizens.